A case report of hyponatremia after surgery for Conn's adenoma. (November 2017) - Furlanis, Giulia; Bernardi, Stella; Cavressi, Monica; Zandonà, Lorenzo; Carretta, Renzo; Fabris, Bruno; Bardelli, Moreno
Primary aldosteronism (PA), also known as Conn's syndrome, is a frequent cause of secondary hypertension. If PA is due to a documented unilateral adrenal adenoma, adrenalectomy is the treatment of choice. Endocrine Society guidelines suggest monitoring potassium after adrenalectomy, while there is no mention of sodium disorders after surgery. Here we report the case of a patient with Conn's syndrome who developed hyponatremia after surgery. This was an unexpected event in the course of the treatment, which sheds light on the fact that low levels of aldosterone strongly influence sodium concentration, and advises clinicians to monitor sodium after adrenalectomy.